2010
DOI: 10.1007/s11664-010-1198-0
|View full text |Cite
|
Sign up to set email alerts
|

Full-Band Monte Carlo Simulation of HgCdTe APDs

Abstract: A full-band Monte Carlo model has been developed for understanding the carrier multiplication process in HgCdTe infrared avalanche photodiodes. The proposed model is based on a realistic electronic structure obtained by pseudopotential calculations and a phonon dispersion relation determined by ab initio techniques. The calculated carrier-phonon scattering rates are consistent with the electronic structure and the phonon dispersion relation, thus removing adjustable parameters such as deformation potential coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…[29][30][31][32][33] In Ref. 3 we reported the results of a one-dimensional Monte Carlo analysis performed on the device structure grown by Derelle et al 9 We have shown that our model satisfactorily reproduces the measured gain and noise characteristics of this device. Although one-dimensional (1D) models are useful to understand the physics of these kinds of devices, they cannot capture the more complex carrier dynamics that takes place in realistic 2D and three-dimensional (3D) structures; for example, it is not possible to evaluate the position-dependent gain or to study edge effects.…”
Section: Numerical Modelmentioning
confidence: 58%
See 3 more Smart Citations
“…[29][30][31][32][33] In Ref. 3 we reported the results of a one-dimensional Monte Carlo analysis performed on the device structure grown by Derelle et al 9 We have shown that our model satisfactorily reproduces the measured gain and noise characteristics of this device. Although one-dimensional (1D) models are useful to understand the physics of these kinds of devices, they cannot capture the more complex carrier dynamics that takes place in realistic 2D and three-dimensional (3D) structures; for example, it is not possible to evaluate the position-dependent gain or to study edge effects.…”
Section: Numerical Modelmentioning
confidence: 58%
“…HgCdTe-based avalanche photodetectors (APD) provide the best performance as they are characterized by high sensitivity and gain while exhibiting very low multiplication noise. [1][2][3] These features are intimately related to the material properties of HgCdTe alloys with cadmium concentrations below 53%. In fact, for these alloys, the impact ionization process is due almost exclusively to electrons, while holes do not contribute.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is of interest to observe how the alloy scattering rate compares for two other band models used recently 6,22 . Table 2 shows the electron alloy scattering rates at four electron energies referenced to the conduction band edge.…”
Section: Alloy No Alloymentioning
confidence: 99%